2021
DOI: 10.1021/acs.energyfuels.0c03647
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Thermophysical Properties and Phase Change Behavior of Expanded Vermiculite-Based Organic Composite Phase Change Materials

Abstract: In this study, the optimized expanded vermiculite (EVM) was used as the matrix and a series of novel form-stable composite phase change materials (fs-CPCMs) were prepared by the physical impregnation method. The results showed that acid leaching and organic intercalation EVM had a better package effect (≥74.9 wt %) and heat storage capacity (≥139.2 J/g) compared with EVM, which showed a good optimization effect, revealing that proper modification treatment was beneficial to the improvement of the thermophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The relationship between the relative crystallinity ( X T ) and time ( t ) or temperature ( T ) could better illustrate the nonisothermal crystallization behavior of octadecane in the EVMs and modified EVMs pores, 17 and their values could be derived from the eqs 2 and 3 . where X T represents relative crystallinity of PCMs, the d H C /d T is the heat flow of crystallization, T B and φ are the temperature at which crystallization begins and cooling rate in the cooling process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the relative crystallinity ( X T ) and time ( t ) or temperature ( T ) could better illustrate the nonisothermal crystallization behavior of octadecane in the EVMs and modified EVMs pores, 17 and their values could be derived from the eqs 2 and 3 . where X T represents relative crystallinity of PCMs, the d H C /d T is the heat flow of crystallization, T B and φ are the temperature at which crystallization begins and cooling rate in the cooling process.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the relative crystallinity ( X T ) and time ( t ) or temperature ( T ) could better illustrate the nonisothermal crystallization behavior of octadecane in the EVMs and modified EVMs pores, and their values could be derived from the eqs and . where X T represents relative crystallinity of PCMs, the d H C /d T is the heat flow of crystallization, T B and φ are the temperature at which crystallization begins and cooling rate in the cooling process. T and t represent any temperature and the cooling time in the crystallization process, the half crystallization time ( t 1/2 ) of octadecane and EVM-based fs-CPCMs could be obtained from Figure and Figure , respectively, and the data are summaried in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase transition process of the composite PCM was investigated using crystallization kinetics, and the results showed that the aerogel skeleton had a heterogeneous nucleation effect on the crystallization of LA, which increased the crystallization rate of LA under non-isothermal and isothermal conditions. Song et al [27] prepared a new shape-stable composite phase change material using the optimized expanded vermiculite (EVM) as a support material. The nonisothermal crystallization kinetics showed that the optimized EVM could effectively reduce the activation energy of nucleation and improve the crystallization and nucleation process of PEG.…”
Section: Introductionmentioning
confidence: 99%